2019
DOI: 10.1016/j.molcel.2019.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Causing Mutations in SF3B1 Alter Splicing by Disrupting Interaction with SUGP1

Abstract: SF3B1, which encodes an essential spliceosomal protein, is frequently mutated in myelodysplastic syndromes (MDS) and many cancers. However, the defect of mutant SF3B1 is unknown. Here, we analyzed RNA sequencing data from MDS patients and confirmed that SF3B1 mutants use aberrant 3 0 splice sites. To elucidate the underlying mechanism, we purified complexes containing either wild-type or the hotspot K700E mutant SF3B1 and found that levels of a poorly studied spliceosomal protein, SUGP1, were reduced in mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
155
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(165 citation statements)
references
References 74 publications
(112 reference statements)
9
155
1
Order By: Relevance
“…Importantly, the differentially expressed genes and aberrant splicing events observed in cells with disease-related SF3B1 point mutations appear to be different from those observed upon depletion of SF3B1 [22,23], stressing the fact that SF3B1 mutants bear specific functions. Interestingly, Zhang et al recently reported that disease-causing mutations in SF3B1 alter splicing by disrupting interaction with the spliceosomal protein SUGP1 [24], providing a possible mechanistic explanation for the phenotype of SF3B1 point mutants. Moreover, silencing of SF3B1 by shRNA alters the proliferation of erythroid progenitors in vitro [23] and in vivo in a mouse model [25], highlighting its essential role during erythropoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the differentially expressed genes and aberrant splicing events observed in cells with disease-related SF3B1 point mutations appear to be different from those observed upon depletion of SF3B1 [22,23], stressing the fact that SF3B1 mutants bear specific functions. Interestingly, Zhang et al recently reported that disease-causing mutations in SF3B1 alter splicing by disrupting interaction with the spliceosomal protein SUGP1 [24], providing a possible mechanistic explanation for the phenotype of SF3B1 point mutants. Moreover, silencing of SF3B1 by shRNA alters the proliferation of erythroid progenitors in vitro [23] and in vivo in a mouse model [25], highlighting its essential role during erythropoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…SF3b1/Hsh155 is no exception, and cryo-EM analysis of yeast and human spliceosome structures have revealed a number of splicing factors which interact with the SF3b1/Hsh155 HR domain [11] Many of these interactions are transient and likely occur consecutively in an ordered fashion: the HR binds to and then releases Prp5 during spliceosome assembly [9, 21] the HR then interacts with Prp3 in B complex spliceosomes before activation and release of the U4 snRNP (including Prp3) [30], and finally Prp2 docks onto the HR to release U2 proteins including SF3b1/Hsh155 prior to splicing catalysis [14, 15] The ability of the Hsh155 V502F mutation studied here as well as other MDS-mutations in Hsh155 [9, 21] to change yeast two-hybrid and genetic interactions with these splicing factors suggests that SF3b1 mutations can perturb splicing at multiple stages. While most models for SF3b1 dysfunction in cancer have focused on steps involved in BS recognition and U2 loading [19, 20, 22], it is possible that some degree of splicing dysregulation occurs through disruption of later steps. For example, some alternative BS may be used due to their ability to assemble spliceosomes that can be successfully activated through altered interactions between SF3b1 and the human homologs of Prp2 and/or Prp3.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms have been proposed to describe how MDS mutations in SF3b1 ultimately lead to selection of alternative BS. These mutations may influence splicing by altering interactions with Prp5 or the human splicing factor SUGP1 [22], disrupting SF3b1 conformational change, or by perturbing the direct interactions between the intronic pre-mRNA and SF3b1 itself. It is possible that several of these mechanisms may work in concert to promote usage of alternative BS.…”
Section: Introductionmentioning
confidence: 99%
“…The recognition sequence of RBM17 overlaps with the target sequence of the cryptic exon suppressed by TDP-43. U2 snRNP is also believed to be involved in the repression of cryptic splice site recognition [60][61][62][63][64]. These potential but inactive splice sites can be recognized when an authentic strong splice site is mutated or when there are defects in the hnRNPs and some RBPs [59].…”
Section: Cryptic Splicingmentioning
confidence: 99%
“…However, it was unknown how SF3B1 mutations affect the protein interactions in the spliceosome because hotspot mutations did not affect the stability of the SF3B1-U2AF complex and the affinity with RNA. Recently, it was reported that hotspot mutations in SF3B1 specifically disrupted the interaction with the spliceosomal protein, SURP and the G-patch domain-containing 1 (SUGP1), without the interference of other SF3B1-associated proteins [64]. SUGP1, previously known as splicing factor 4 [102], has two tandem SURP domains and a G-patch domain.…”
Section: Sf3b1mentioning
confidence: 99%